Interior intimo meo: Rowan Williams on the Self - Delport, Khegan Marcel (Stellenbosch theological journal, 2018)
In this essay we discuss Williams's notion of the self as a social mediation. The argument is made that from early on Williams was influenced by different streams of thought that directed him to analogous conclusions regarding language and personhood. I will show that through internalizing of Augustine, Wittgensteinian philosophy and certain strands of Eastern Orthodox thought, Williams came to an understanding of language that was grounded in the particulars of human interaction, one that is finally kenotic since the imago dei is reflective of the imago trinitatis. It is within this context that one should place Williams own relationally-centred, non-egocentric construal of human personhood that finds its centre in the dynamic exteriority of love.